Analysis of Completeness and Suitability of Outpatient Prescriptions at Islamic Hospital “X” Malang - Yudi Purnomo (STIKES Rumah Sakit Anwar Medika, 2022)
Irrational drug prescribing is a serious problem in health services in Indonesia. Factors that contribute to this condition are incomplete and inappropriate prescriptions, especially in the pharmaceutical and clinical aspects. This study aims to assess the level of completeness and suitability of outpatient prescribing at the “X” Islamic Hospital of Malang. The study design was retrospective using prescription data for 2 months with predetermined criteria. The level of completeness and suitability of prescriptions was analyzed from the pharmaceutical and clinical aspects. The data obtained are expressed in percentages. The results of the analysis of 942 outpatient prescription sheets for 2 months obtained the level of completeness and suitability of prescriptions (82.16%). The level of completeness and suitability of the pharmaceutical aspects, namely drugs (99.78%), drug dosage forms and route of administration (99.78%). From the clinical aspect, namely the dose of the drug (86.7%), the frequency and duration of drug administration (76.7%), the time of administration of the drug (47.8%), and drug duplication (0.88%) and polypharmacy (1.5%). The level of completeness and suitability of outpatient prescribing at the “X” Islamic Hospital of Malang is generally good but the timing of drug administration and the frequency and duration of drug administration need to be improved